Autism is the future: the evolution of a different type of intelligence - Guo, Ling (e-Pedagogium, 2020)
Thurman, Marlo, Payne. Autism is the Future: The Evolution of a Different Type of Intelligence.Arlington, TX: Future Horizons Inc., 2019. 207 pages. ISBN 9781935567172